2022
DOI: 10.3389/fbioe.2022.858610
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Tendon Shear Wave Velocity Is Higher and has Different Regional Patterns in Elite Competitive Alpine Skiers than in Healthy Controls

Abstract: Competitive alpine skiers are exposed to enormous forces acting on their bodies–particularly on the knee joint and hence the patellar tendon - during both the off-season preparation and in-season competition phases. However, factors influencing patellar tendon adaptation and regional pattern differences between alpine skiers and healthy controls are not yet fully understood, but are essential for deriving effective screening approaches and preventative countermeasures. Thirty elite competitive alpine skiers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…To enable intra-and inter-individual comparisons of the local SWV, the retrieved volume can be mapped into an abstracted representation of the muscle of study in reference to selected geometrical and anatomical features. A similar approach has already been shown to be technically feasible, reproducible and clinically significant in previous studies for tendons (Götschi et al, 2021;Götschi et al, 2022a;Götschi et al, 2022b). However, it is not clear a priori whether this is directly transferable to muscle tissue, particularly given the much larger volumes of interest.…”
Section: Introductionmentioning
confidence: 90%
“…To enable intra-and inter-individual comparisons of the local SWV, the retrieved volume can be mapped into an abstracted representation of the muscle of study in reference to selected geometrical and anatomical features. A similar approach has already been shown to be technically feasible, reproducible and clinically significant in previous studies for tendons (Götschi et al, 2021;Götschi et al, 2022a;Götschi et al, 2022b). However, it is not clear a priori whether this is directly transferable to muscle tissue, particularly given the much larger volumes of interest.…”
Section: Introductionmentioning
confidence: 90%
“…A recent study suggested that young males may have different mechanical properties in the patellar tendon assessed by shear wave elastography when compared with young females 15 . To our knowledge, however, no study has evaluated the in vivo morphology and mechanical properties of the patellar tendon segmented mediolaterally into three regions in young males and females.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that young males may have different mechanical properties in the patellar tendon assessed by shear wave elastography when compared with young females. 15 To our knowledge, however, no study has evaluated the in vivo morphology and mechanical properties of the patellar tendon segmented mediolaterally into three regions in young males and females. The purpose of this study was to compare the thickness, length, viscosity, and shear modulus of the medial, central, and lateral regions of healthy patellar tendons of young males and females in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The patellar tendon is a linear structure composed of a superficial and a deep layer that runs in parallel from the patella to the tibia without direct muscle insertions [ 1 ]. It is capable of supporting large volumes of weight and is one of the tendons responsible for providing stability and extension of the knee [ 2 , 3 ]. Due to its morphology and adaptive properties, the tendon exhibits the capacity to respond to both intrinsic and extrinsic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its morphology and adaptive properties, the tendon exhibits the capacity to respond to both intrinsic and extrinsic stimuli. The patellar tendon can undergo thickening and remodeling due to the pull that occurs by repeated forces [ 2 ].…”
Section: Introductionmentioning
confidence: 99%